Comparison of body composition, cardiorespiratory, and neuromuscular adaptations induced by three different high intensity training protocols - Corentin Scoubeau; Julie Carpentier; Stéphane Baudry; Vitalie Faoro; Malgorzata Klass (Physiological Reports)
Abstract This study investigated body composition, cardiorespiratory, and neuromuscular adaptations induced by three high intensity trainings easy to fit into daily routine. Thirty‐seven adults participated in one of the following 8‐week interventions: vigorous intensity continuous training (VICT; 28 min at 70% of peak oxygen uptake [VO2peak]), long interval high intensity interval training (LI‐HIIT; 6 × 2 min at 85% VO2peak), or short interval HIIT (SI‐HIIT; 12 × 30 s at 125% maximal power output). Heart rate (HR) and rating of perceived exertion (RPE) were measured during sessions. Pre‐ and post‐intervention assessments included fat and lean mass, cardiopulmonary exercise testing, knee extensors maximal isometric torque, voluntary activation, and endurance during a submaximal contraction. Compared to SI‐HIIT and VICT, LI‐HIIT sessions were characterized by a shorter duration, a similar time spent above 90% HRmax, but a higher RPE (p < 0.05). VO2peak and muscle endurance increased respectively by 14% and 12%, while knee extensors torque, voluntary activation, and lean mass increased to a lesser extent (1%–3%) after the interventions (ANOVA time‐effect, all p < 0.05). There was no significant difference between the modalities (intervention × time interaction, all p > 0.05). In conclusion, comparable body composition, cardiorespiratory, and neuromuscular adaptations were induced by the three high intensity training protocols, while RPE was higher during LI‐HIIT sessions.